Electric‐Field‐Regulated Energy Transfer in Chiral Liquid Crystals for Enhancing Upconverted Circularly Polarized Luminescence through Steering the Photonic Bandgap. Issue 24 (6th May 2020) - Yang, Xuefeng; Zhou, Minghao; Wang, Yafei; Duan, Pengfei
Abstract: Circularly polarized luminescent materials with high dissymmetry factor ( g lum ) have been attracting increasing attention due to their distinctive photonic properties. In this work, by incorporating upconversion nanoparticles (UCNPs) and CsPbBr3 perovskite nanocrystals (PKNCs) into a chiral nematic liquid crystal (N*LC), enhanced upconverted circularly polarized luminescence (UC‐CPL) based on a radiative energy transfer (RET) process from UCNPs to CsPbBr3 PKNCs is successfully implemented. By locating the emission peak of CsPbBr3 PKNCs at the center of the photonic bandgap of N*LC, the maximum g lum value of UC‐CPL can be amplified to an extremely large value of 1.1. Meanwhile, upconverted emission of UCNPs can be significantly enhanced due to the band edge enhancement effect of the N*LC, subsequently enhancing the emission of the CsPbBr3 PKNCs through the RET process. In addition, an applied electric field can switch the upconverted emission of the UCNPs, as well as the RET process, enabling an electric‐field‐controlled UC‐CPL switch. Abstract : Upconverted circularly polarized luminescence (UC‐CPL) of CsPbBr3 perovskite nanocrystals based on a radiative energy‐transfer process from upconversion nanoparticles can be realized in chiral nematic liquid crystals. A very large dissymmetry factor of around 1.1 for the UC‐CPL is obtained. In addition, a voltage‐force‐regulated chiroptical switch of UC‐CPL is realized.